2022
DOI: 10.1039/d1na00682g
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of epigenetics in the field of nanoparticles

Abstract: Nanoparticles (NPs) have become a very exciting research avenue, with multitudinous applications in various fields, including the biomedical one, whereby they have been gaining considerable interest as drug carriers able...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 132 publications
(237 reference statements)
0
8
0
Order By: Relevance
“…Previous studies related to the AgNPs mediated epigenetic toxicity mainly focuses on DNA and histone modifications, or alterations of miRNA expression. 34–37 In this unique research, we have shown that GO-AgNPs cause differential expression of circRNAs and lncRNAs in RFFCs. In addition, we have constructed a comprehensive network map of circRNA–miRNA–mRNA that shows the potential scenario of how circRNAs are regulating gene expression by interacting with the miRNAs.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies related to the AgNPs mediated epigenetic toxicity mainly focuses on DNA and histone modifications, or alterations of miRNA expression. 34–37 In this unique research, we have shown that GO-AgNPs cause differential expression of circRNAs and lncRNAs in RFFCs. In addition, we have constructed a comprehensive network map of circRNA–miRNA–mRNA that shows the potential scenario of how circRNAs are regulating gene expression by interacting with the miRNAs.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, current studies have proposed that ncRNAs combined with biocompatible nanoparticles (NPs) can offer better therapeutic properties. Using NPs as delivery vectors can reduce drug toxicity, facilitate targeted drug release, and increase drug bioavailability, which provides an optimized therapeutic strategy for the cardiovascular field ( 125 , 128 130 ). In addition, with the production of proteasome inhibitors, the UPS offers a new therapeutic frontier.…”
Section: Prognostic and Therapeutic Targetsmentioning
confidence: 99%
“…In light of this, ncRNAs are increasingly proposed for therapeutic applications in association with biocompatible nanoparticles (NPs). These are small particles with a diameter ranging from 1 to 100 nm, already effectively used for the transport and release of antibiotics, anticancer drugs, and for viral or non-viral genes to the site of interest without being recognized by the immune system [84].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%